2018
DOI: 10.1097/meg.0000000000001175
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of inadequate bowel preparation for colonoscopy: a systematic review and meta-analysis

Abstract: The aim of this study was to investigate factors contributing to poor bowel preparation in patients undergoing colonoscopy procedures. We used a reproducible search strategy to identify studies, searching 10 medical databases, including PubMed, Ovid, Medline, and Cochrane Library Database for reports published between 2000 and 2016. Fully published studies, evaluating risk factors for inadequate bowel preparation, were included. Two reviewers independently scored the identified studies for methodology and abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 65 publications
9
100
0
1
Order By: Relevance
“…In the current study, we demonstrated that several of the indications of the procedure and the clinical settings were linked with poor preparation. Constipation was significantly associated with inadequate cleansing (OR 1.373, 95%CI 1.24-1.519; P<0.01), consistent with similar findings from other studies [32]. Likewise, patients with rectal bleeding were less adequately prepared (OR 1.473, 95%CI 1.355-1.602; P<0.01), apparently because of the urgent nature of procedures in this setting.…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, we demonstrated that several of the indications of the procedure and the clinical settings were linked with poor preparation. Constipation was significantly associated with inadequate cleansing (OR 1.373, 95%CI 1.24-1.519; P<0.01), consistent with similar findings from other studies [32]. Likewise, patients with rectal bleeding were less adequately prepared (OR 1.473, 95%CI 1.355-1.602; P<0.01), apparently because of the urgent nature of procedures in this setting.…”
Section: Discussionsupporting
confidence: 88%
“…This study suggested that male sex was associated with an increased risk of suboptimal colon preparation, in line with prior findings (Cheng et al, ; Lebwohl, Wang, & Neugut, ). A possible explanation was that compliance with taking laxatives is poorer among men than among women (Lebwohl et al, ; Mahmood et al, ). Furthermore, constipation is considered an independent risk factor for inadequate colon preparation (Cheng et al, ), which is inconsistent with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, 12-22% of excess colonoscopy-related costs are due to suboptimal bowel preparation (Byrne, 2002). Hospitalized patients are at a higher risk for poor bowel preparation than outpatients because they are generally older and weaker (Chorev et al, 2007;Mahmood, Farooqui, & Madhoun 2018;Mcnabb-Baltar et al, 2016). One prior study revealed that the rate of adequate bowel preparation was only 50% in hospitalized patients (Ness et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…An adequate bowel preparation is essential in providing satisfactory visualization of the colonic mucosa, to optimize lesion detection, and to make a safe therapeutic intervention (2)(3)(4). Despite this, unfortunately, many patients cannot comply with the bowel cleaning regimens because of strict dietary modifications that affect their preprocedural quality of life and the large volume of flavorless laxative solutions (5,6). Moreover, patients having an inadequate bowel cleaning need to repeat similar preparation steps before the next examination (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients having an inadequate bowel cleaning need to repeat similar preparation steps before the next examination (6,7). This also means that the risks associated with endoscopic investigation and anesthesia increase, and the procedure cost doubles (5,7).…”
Section: Introductionmentioning
confidence: 99%